Palgrave Advances in Continental Political Thought
VI, 330 p.
Keywords: An accessible, higher-level introduction to a key selection of continental European thinkers from Spinoza to Zizek. Covering 'classical' exponents of the tradition such as Hegel and Marx, 'moderns' like Gramsci and Habermas and 'postmoderns' like Lacan and Deleuze, the volume introduces the main ideas of each thinker and reflects on their enduring theoretical relevance. The impressive breadth and contemporary angle make this a unique, up-to-date collection that will be invaluable to students and teaching staff alike.